Improvement of iron content of crackers using powdered lupo lupo (Alternanthera sessillis) leaves. - Javier, Cherry Ann Nicopior
The study focused on the improvement of crackers with the use of powdered lupo lupo leaves. Three formulations of crackers with 5%, 10% and 15% lupo lupo powder, designated as F1, F2 and F3, respectively were prepared and subjected to rank test for preference. Kruskal-Wallis rank sum test at 5% level of significance revealed that the three formulations were significantly different. Lupo lupo crackers prepared from F1 (5% lupo lupo powder) was the most preferred formulation. Lupo lupo crackers had water activity content of 0.46, hardness of 4.05N and iron content of 0.25477 mg/g. Lupo lupo cracker was measured to contain 6.00% moisture, 2.10% ash, 0.98% crude protein, 7.38% crude fat, 0.32% crude fiber and 83.68% carbohydrates. Two sample t-test revealed a significant increase in the iron content and the crude fiber content of the crackers with the addition of lupo lupo powder. Lupo lupo cracker was described as light green in color, has slightly salty taste, crunchy texture, slightly perceptible lupo lupo flavor and not perceptible lupo lupo odor. It was highly acceptable among children and adults, 62% rated the product like very much. Out of 105 respondents, 73.3% rated the product like very much and 21.9% rated the lupo lupo cracker like moderately.